2017
DOI: 10.3389/fmars.2017.00386
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Seasonal Cycles of Phytoplankton Chlorophyll, Aerosols, Winds and Sea-Surface Temperature off Somalia

Abstract: In climate research, an important task is to characterize the relationships between Essential Climate Variables (ECVs). Here, satellite-derived data sets have been used to examine the seasonal cycle of phytoplankton (chlorophyll concentration) in the waters off Somalia, and its relationship to aerosols, winds and Sea Surface Temperature (SST). Chlorophyll-a (Chl-a) concentration, Aerosol Optical Thickness (AOT), Ångström Exponent (AE), Dust Optical Thickness (DOT), SST and sea-surface wind data for a 16-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…The OC-CCI surface chlorophyll-a (Chl_a) concentration data from version 3.1 (Sathyendranath et al, 2018), for the period 1998 to 2014 has been used in this study. OC-CCI Chl_a data has already been verified and used to estimate the surface Chl_a concentration in the Arabian Sea by several authors (eg: Shafeeque et al, 2017;Monolisha et al, 2018;Smitha et al, 2019;Menon et al, 2019). SST data are based on extended reconstructed SST (ERSST v4) (Huang et al, 2015;Liu et al, 2015), produced on a 2°x2° grid derived from the International Comprehensive Ocean-Atmosphere Dataset (ICOADS).…”
Section: Datamentioning
confidence: 99%
“…The OC-CCI surface chlorophyll-a (Chl_a) concentration data from version 3.1 (Sathyendranath et al, 2018), for the period 1998 to 2014 has been used in this study. OC-CCI Chl_a data has already been verified and used to estimate the surface Chl_a concentration in the Arabian Sea by several authors (eg: Shafeeque et al, 2017;Monolisha et al, 2018;Smitha et al, 2019;Menon et al, 2019). SST data are based on extended reconstructed SST (ERSST v4) (Huang et al, 2015;Liu et al, 2015), produced on a 2°x2° grid derived from the International Comprehensive Ocean-Atmosphere Dataset (ICOADS).…”
Section: Datamentioning
confidence: 99%
“…They are also important players in the cycling of other elements in the ocean, including nitrogen, silica, and iron [3]. Phytoplankton are understood to impact atmospheric processes such as formation of aerosols through complex pathways [4,5,6,7]. Understanding phytoplankton is fundamental to anticipating how the marine ecosystem might respond to climate variability and climate change [8].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation and lag/lead between the variables are estimated at 95 % confidence level. The phase relationships between the variables can help identify the underlying causes (Shafeeque et al, 2017) and therefore, we have used the phase relationships to find the correlation between the variables. The Chl-a is positively correlated with WS and NPP with correlations of 0.90 and 0.98 in AS1 and 0.66 and 0.97 in BB1.…”
Section: Statistical Analysis On Interannual Variability Of Nppmentioning
confidence: 99%
“…The connection between phytoplankton bloom and dust deposition over Central AS was analyzed by Banerjee and Prasanna Kumar (2014) and found that blooms cannot be fully described by injection of nutrients by processes such as advection and mixing in the upper ocean. Shafeeque et al (2017) compared the seasonal cycles of phytoplankton with SST, Aerosol Optical Depth (AOD), and winds off Somalia. The productivity in the high-nutrient low chlorophyll (HNLC) regions of oceans is directly affected by the iron supply (Jickells et al, 2005).…”
Section: Introductionmentioning
confidence: 99%